Synthesis of 3,5-Diaryl-4-Benzoyl-1-Pyridoyl-Δ2-Pyrazolines - Kadu, M.V.; Jamode, V.S. (Asian Journal of Chemistry, 2010)
Some new 3,5-diaryl-4-benzoyl-1-pyridoyl-Δ2 -pyrazolines (3)have been synthesised by the action of isoniazid on 3-aroyl tlava-nones(2) in pyridine medium. Structures of these compounds havebeen established by spectral analysis (NMR, IR and UV) and elementalanalysis.